ACTION - DEVELOPMENT OF CORRECTION OF SPEECH DEFICITS IN PRESCHOOL CHILDREN WITH INJURIES OF SUPPORTING ORGANS (BTSF) - Suvankulova Shakhnoza Karimkulovna (Zeta Repository, 2023)
The peculiarity of cognitive, speech and motor development of preschool children with motor impairment leads to persistent disturbances in their communication and difficulties in using verbal and non-verbal communication. Study of the state, features of formation and dynamics of verbal and non-verbal communication in preschool children with movement injuries.